Pembelajaran IPS dengan Model Problem Based Learning (PBL) di Sekolah Dasar - Adriani, Rita; s, Farida; Arwin, Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This research was intended to improve the studens’ learning achievement in the Social Studies by using Problem-Based Learning model in the fourth grade of  SDN 09 Air Tawar Barat Padang. This was a classroom action research which used qualitative and quantitative approaches. The subject of the research was the fourth grade students of  SDN 09 Air Tawar Barat. Based on the result of data analysis, it was figured out that from the first cycleto the second one, the average score for the Lesson Plan improved from 69,64% into 85,8%, the teacher’s aspect improved from 85,71%, and the student’s aspect improved from 70,54% into 87,50%. In addition, the student’s learning achievement improved from 71,09 into 87,50%. keywords: IPS learning outcomes, problem based learning model